ANALISIS KEUNTUNGAN PEMELIHARAAN TERNAK SAPI DI KECAMATAN SULUUN TARERAN KABUPATEN MINAHASA SELATAN - Tumober, Jimmy Ch.; Makalew, A.; Salendu, A. H.S.; Endoh, E. K.M (ZOOTEC, 2014)
ABSTRACT PROFIT ANALYSIS OF BEEF FARMING AROUND SULUUN TARERAN DISTRICT IN SOUTH MINAHASA REGENCY. Generally, communities of Suluun Tareran district were household farmers. Beef cattle populations in this area were about 308 head spreading at eight villages. The problem was how much the production cost (feeding, labor, and other feed supplement) do affect the profit of beef farming around this area. The objective of this study was to evaluate effect of production cost on income and profit of beef farming system in Suluun Tareran district of South Minahasa regency. Research was conducted using survey method. Data were found from two sources including primer and secondary data sources. Samples of respondence were determined by purposive sampling method. The total of 30 household farmers were used in this study. Results showed that grass feeding of the animals was not bought by farmers, except in dry season. Average production cost of beef cattle at research location were Rp. 6,756,215,67 per year of 3-4 animals consisted of feed cost (50,20%), labor cost (46,36%) and feed supplement (1,44%). Production cost affected significantly (tcalc. = 0.0003) profit level of beef cattle farming in Suluun Tareran district. Key word: Production cost, profit level, beef cattle farming, Suluun Tareran district.